Regional segregation of chiral alcohol on polyoxotitanate cluster. (1st February 2023) - Li, Huan; Li, Xin; Wang, Yu-Xin; Li, Ting; Dong, Jing; Liang, Linfeng; Cui, Xiaoqin
Graphical abstract: The enantiomers of chiral alcohols with bulky groups are separated on the opposite sides of the Ti6 cluster. Abstract: The conformational analysis of peripheral ligands on the polyoxotitanate has drawn much less attention than its application in photocatalysis. In this study, a series of polyoxotitanate clusters with the same Ti6 kernels but different alcohol ligands have been synthesized and characterized. A systematic configurational analysis has revealed that when steric demanding enantiomeric alcohol ligands are confined within a narrow space as on the hexanuclear Ti6 clusters, they can achieve regional separation on different sides of the clusters.